Coupling of Silk Fibroin Nanofibrils Enzymatic Membrane with Ultra‐Thin PtNPs/Graphene Film to Acquire Long and Stable On‐Skin Sweat Glucose and Lactate Sensing. Issue 3 (15th January 2021) - Liu, Xiaotian; Zhang, Wenli; Lin, Zaifu; Meng, Zhaohui; Shi, Chenyang; Xu, Zhijun; Yang, Likun; Liu, Xiang Yang
Abstract: The applications of enzymatic biosensors are largely limited by their relatively poor stability and short lifespan. Herein, a bio‐active porous enzymatic nanofiber (PEN) membrane composed of silk fibroin nanofibrils (SFNFs) and enzymes is developed to effectively retain the enzymes in the 3D space. The 3D functional scaffolds formed by SFNFs can immobilize enzymes and provide a large surface area for molecular/ion diffusion and biochemical reactions. The PEN membrane is subsequently attached to an ultra‐thin PtNPs/graphene (Pt‐G) nanocomposite film to facilitate the electron transport between the enzymes and electrodes, permitting highly effective glucose and lactate sensing with long and stable performance. The as‐assembled glucose and lactate sensors demonstrate high sensitivity, good cyclic reproducibility, and in particular long‐term stability of up to 25 and 23.6 h, respectively. These glucose sensors have a working life that is ≈1.25‐times longer than that of the best available sensors reported so far. Moreover, a wearable platform based on the sensors is developed for real‐time analysis of sweat during outdoor exercising to transmit signals to a mobile handset. The high sensitivity, comfort and long‐term stability of the device can benefit for long‐term in‐line surveillance of physiological conditions. Abstract : 3D functional scaffolds of porous enzymatic nanofibers (PENs) effectively retain enzymes and provide large surface area for molecular/ion diffusion and biochemical reactions. The PEN membrane further attaches to the Pt‐G nanocomposite film to facilitate the electron transport, which permits highly effective glucose and lactate sensing with long and stable performance.